CRIMINOLOGICAL FEATURES ORGANIZED COUNTERFEITING IN THE DIGITAL AGE - Jamaludin Kh. Umakhanov; Maya G. Dieva (Russian Studies in Law and Politics)
Relevance. In recent years, in the field of counterfeiting, organized groups have been using the possibilities of digital technologies, which contributes to changing the structure of crime in this category, associated with erasing the criminal relationship and personal interaction of accomplices.